Pathological findings following hysterectomy in women 45 years and older, and their relationship to menopausal status - Shahid, Ruqaiya (International Journal of Pathology, 2023)
Background: Menopause is the physiological cessation of the reproductive cycle in elderly women; hysterectomy is surgical removal of the uterus and cervix. It was hypothesized that older premenopausal and postmenopausal women experienced different pathological findings following hysterectomies. To identify common pathological findings in hysterectomy specimens of women 45 years of age and older, and to correlate these findings with the women’s menopausal status.Material and Methods: This cross-sectional study was conducted at the Histopathology Department of Dow international Medical College, Dow University of Health Sciences. Data of the hysterectomy specimens of women 45 years and older, reported during the three years from 2018-2020, were reviewed from the pathology reports and analyzed using SPSS (IBM v26). Results: There were 525 hysterectomy samples from women 45 years of age and older. The mean age was 52.40 (+7.89) years; 236 (44.95%) of the women were postmenopausal, 207 (39.42%) were premenopausal, menopausal status was not known for 82 (15.62%). Abnormal uterine bleeding was the most frequent clinical presentation, reported in 256 (48.76%) women. Common benign uterine pathologies included leiomyomata and adenomyosis in 350 (66.67%) of the women, endometrial atrophy in 114 (21.71%), uterovaginal prolapse in 104 (20.0%), and endometrial polyp in 97 (18.48%) of the women. Endometrioid carcinoma of the endometrium affected 23 (4.38%) women, and serous carcinoma of the ovary involved 10 (2.50%). Endometrial atrophy (Fisher exact, p=0.00001), uterine prolapse (χ2, p=0.00001), endometrial cancer (Fisher exact, p=0.0002), ovarian cancer (Fisher exact, p=0.0008) and tubal cancer (Fisher exact, p=0.015) were significantly associated with postmenopausal women, whereas leiomyoma and adenomyosis had a higher frequency in premenopausal women (χ2, p=0.00001).Conclusion: Most common pathological findings were leiomyomata and adenomyosis in premenopausal women. Endometrial atrophy and uterine prolapse in postmenopausal women. There was a significant association between postmenopausal status and endometrial, ovarian, and tubal malignancies.